Experimental reconstruction of Sgraffito Pottery Known as Aqkand Type - atefe fazel; mehdi razani (Dānishhā-yi būmī-i Īrān, 2023)
This research has been done, with the purpose of reconstructing the glaze manufacturing technology based on historical formulas with an emphasis on the carved pottery of the middle ages of the Islamic period and based on the experimental- technical method. The main questions are: 1) What was the process of development and formation of sgraffito pottery until its peak? 2)According to the available information regarding the technical operation of sgraffito pottery, how can it be revived? In this article, the history and techniques of sgraffito pottery and its developments in Iran, as well as the stages of making scratched pottery, with an emphasis on the Aqhkand type pottery, are discussed and based on this, by designing experimental-technical tests, prototyping, and testing the body of pottery and glaze has been carried out, based on observations and visual study Aqhkand pottery collection. The results showed that by considering some factors such as: coordination of the appropriate clay body, the coordination of white slip with the colored glaze, the coordination of the colored glaze with the transparent glaze coating on the body of pottery controlling the formula and amounts of the materials, the desired glaze can be restored and revived.